The influence of student factors on students’ achievement in the Trends in International Mathematics and Science Study in Abu Dhabi Emirate Schools - Wardat, Yousef; Belbase, Shashidhar; Tairab, Hassan; Takriti, Rachel Alison; Efstratopoulou, Maria; Dodeen, Hamza (Frontiers in Psychology, 2023)
This study aimed to investigating student factors on performance in mathematics in Abu Dhabi schools in the United Arab Emirates. We used the secondary data from the Trends of International Mathematics and Science Study (TIMSS) 2015 that included 4838 eighth grade students from 156 schools from Abu. The data from the student questionnaire in TIMSS 2015 were subjected to principal components analysis (PCA). The five factors generated from the student questionnaire included Safety and Behavior, Classroom Mathematics, Environment, Student Attitudes towards Mathematics, and Technology and Resources. Effect of these factors on students’ achievement were examined by multiple regression analysis. All of these factors had a significant impact on student achievement in the TIMSS 2015. Pedagogical and policy implications of the findings have been discussed.